2017
DOI: 10.1039/c7tx00180k
|View full text |Cite
|
Sign up to set email alerts
|

Tributylphosphate (TBP) and tris (2-butoxyethyl) phosphate (TBEP) induced apoptosis and cell cycle arrest in HepG2 cells

Abstract: The purpose of this study was to investigate the cytotoxic effects of tributylphosphate (TBP) and tris (2-butoxyethyl) phosphate (TBEP) and to explore the underlying molecular mechanism focusing on oxidative stress, apoptosis, and cell cycle arrest. The results showed that TBP and TBEP could inhibit cell proliferation, induce cellular reactive oxidative stress, and suppress the mitochondrial membrane potential in HepG2 cells. TBP and TBEP could induce both mitochondrial and p53 mediated apoptosis through diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 53 publications
3
3
0
Order By: Relevance
“…Through the mitochondrial-independent pathway, exogenous chemicals and contaminants stimulate the expression of caspase 8 , which lead to an increase in the caspase 3 levels and apoptosis. Through the mitochondrial-dependent pathway, chemical stimulation causes DNA damage, and the induced DNA damage induces mitochondria to release cytochrome c and thereby induces an increase in caspases 9 and 3 and apoptosis, which is similar to the observation that 50 μM TNBP induces mitochondrial apoptosis in HepG2 cells …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Through the mitochondrial-independent pathway, exogenous chemicals and contaminants stimulate the expression of caspase 8 , which lead to an increase in the caspase 3 levels and apoptosis. Through the mitochondrial-dependent pathway, chemical stimulation causes DNA damage, and the induced DNA damage induces mitochondria to release cytochrome c and thereby induces an increase in caspases 9 and 3 and apoptosis, which is similar to the observation that 50 μM TNBP induces mitochondrial apoptosis in HepG2 cells …”
Section: Discussionsupporting
confidence: 80%
“…33 Similarly, in our previous study, transcriptomics showed that exposure to 40 and 400 μg/L TDCIPP can induce apoptosis and genetic toxicity in Chinese rare minnows. 33 Apoptosis induction has been observed in HepG2 cells exposed to TNBP 41 and in human neuroblastoma (SH-SY5Y) cells exposed to TDCIPP. 42 Therefore, the apoptosis pathway was evaluated in this study as a potential mechanism underlying the response of C. fluminea to TDCIPP and TNBP exposure.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It can be surmised that the prolonged exposure of TEHP at high concentrations surpasses the cellular threshold to fix anomalies and damages, eventually triggering apoptotic cell death. Our finding is in close agreement with previous reports on OPFRs, which also exhibited similar toxic effects at high concentrations after extended exposure time periods [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that ( -)-ICP induces a change in the Bax/Bcl-2 ratio and hepatotoxicity by the sustained activation of JNK [53]. The addition of tributyl phosphate (TBP) and tris (2-butoxy ethyl) phosphate (TBEP) to HepG2 produced ROS overproduction and caused mitochondrial and p53-mediated apoptosis via activation of JNK and ERK1/2 pathways by TBP and activation of the JNK pathway by TBEP [54].…”
Section: Organophosphorus Compound-induced Hepatotoxicity Is Mediatedmentioning
confidence: 99%